The strategy of Two Stay Two Stray to improve EFL students’ reading skill - Diana Fauzia Sari; Siti Sarah Fitriani; Sevty Emafetery (Universitas Syiah Kuala, 2019)
The objectives of this study are to figure out whether the use of Two Stay Two Stray (TSTS) strategy could improve Grade 8 EFL students’ reading skill in a junior high school in Banda Aceh and to find out the students’ perspective about the use of this strategy. One class was randomly chosen as the sample in this study. The data were collected by using tests and questionnaire. The data were both analyzed by using statistical formulas. The results show that the use of TSTS in teaching reading to the Grade 8 students was successful. It can be seen from the mean scores of the experimental class that was 84.70. Moreover, the t-score (6.81) was higher than t-table (2.021), and this indicates that the students in the experimental class who were taught using TSTS got better improvement than before they were taught using this strategy. The results from the questionnaire also revealed that the students’ have positive responses in relation to the use of TSTS because this strategy offered a positive relationship between teacher-students and students-students, and further increase their interest in learning. This led the students to escalate their self-confidence, social interaction, individual accountability, and group skills. A better understanding of the materials taught was also attained because they could learn together as a team.